Time-resolved and temperature tuneable measurements of fluorescent intensity using a smartphone fluorimeter. Issue 11 (5th May 2017) - Hossain, Md Arafat; Canning, John; Yu, Zhikang; Ast, Sandra; Rutledge, Peter J.; Wong, Joseph K.-H.; Jamalipour, Abbas; Crossley, Maxwell J.
Abstract : A smartphone fluorimeter is demonstrated for steady-state and time-resolved fluorescence intensity measurements at tunable temperatures. Abstract : A smartphone fluorimeter capable of time-based fluorescence intensity measurements at various temperatures is reported. Excitation is provided by an integrated UV LED ( λ ex = 370 nm) and detection obtained using the in-built CMOS camera. A Peltier is integrated to allow measurements of the intensity over T = 10 to 40 °C. All components are controlled using a smartphone battery powered Arduino microcontroller and a customised Android application that allows sequential fluorescence imaging and quantification every δt = 4 seconds. The temperature dependence of fluorescence intensity for four emitters (rhodamine B, rhodamine 6G, 5, 10, 15, 20-tetraphenylporphyrin and 6-(1, 4, 8, 11-tetraazacyclotetradecane)2-ethyl-naphthalimide) are characterised. The normalised fluorescence intensity over time of the latter chemosensor dye complex in the presence of Zn 2+ is observed to accelerate with an increasing rate constant, k = 1.94 min −1 at T = 15 °C and k = 3.64 min −1 at T = 30 °C, approaching a factor of ∼2 with only a change in temperature of Δ T = 15 °C. Thermally tuning these twist and bend associated rates to optimise sensor approaches and device applications is proposed.